Characteristics analysis of an extreme heavy rain event in the middle reaches of the Yangtse River from July 4 to 8 in 2020 - Zhiyong HUANG; Jingyu WANG; Wen ZHOU (暴雨灾害, 2021)
Based on Doppler weather radar data, meteorological satellite cloud images, observations from automatic weather station (AWS) and NCEP reanalysis data, we have conducted the analysis of a sustained extra heavy rain event in the middle reaches of the Yangtse River from July 4 to 8 in 2020 including its precipitation characteristics, meso-scale convective systems (MCS) evolution and the distribution of temperature, humidity, vorticity, vertical velocity and other physical quantities on the Meiyu front. The results indicate that the event is characterized by long duration, wide coverage, concentrated rainstorm areas, large accumulated rainfall. This sustained extra heavy rain event is due to the ambient background of a stable Ω-shaped general atmospheric circulation in the mid-and high- latitudes at 500 hPa. The high echo top, great intensity and low centroid of convective cell and the "train effect" are the main reason that leads to the heavy rain event with high intensity. The following are the main characteristics of the physical quantities on the Meiyu front. The Meiyu front formed by pseudo-equivalent potential temperature (θse) from down to up is close to vertical, then the atmospheric stratification in the lower troposphere especially below 850 hPa within front zone is unstable and the wind speed in the low-level front zone is small. The dry and cold air from tropopause in north of 35°N intrudes southerly to the Meiyu front. There is an evolution of convergence in the mid- and low-level and divergence in the upper level and the vertical velocity increasing and then decreasing over the heavy rain center, and positive vorticity transporting to front of the Meiyu front. The horizontal temperature gradient in the lower troposphere of the Meiyu front is very small, and there is a relative low temperature zone in the lower level of the meiyu front zone. There is a certain horizontal specific humidity gradient near the Meiyu front, and that on the north side of the meiyu front is greater.